STUDENŢI DE NOTA ZECE - KULIKOVSKI, Lidia (BIBLIOPOLIS, 2020)
The fundamental unit of the new world is not one organization but the individual. The individual of new world is participative, motivated, capable and eager to engage in activities that concern him, keen to tell their views. Students, being the main subject of this article, never agreed with the assessment methods of their capabilities made by training institutions. They do not like the evaluation methods that do not refl ect their vision and human side, their personality. The experiment conducted with fi rst year masters students, highlights interesting results of student’s personality who has been given the freedom to express their personal development after accumulating knowledge from the university. The method generates a framework for students to see him self as they are without the need or requirement to disclose some of his ego.